2015
DOI: 10.5293/ijfms.2015.8.1.046
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Design of Thrust Ring Pump for Large Hydro Turbine Generator Units

Abstract: Thrust-ring-pump is a kind of extreme-low specific speed centrifugal pump with special structure as numerous restrictions from thrust bearing and operation conditions of hydro-generator units. Because the oil circulatory and cooling system with thrust-ring-pump has a lot of advantages in maintenance and compactness in structure, it has widely been used in large and medium-sized hydro-generator units. Since the diameter and the speed of the thrust ring is limited by the generator set, the matching relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The resultant comparison between the experimental and numerical data showed that both models can be used to analyze the cooling system. Lai et al[24] conducted one-dimensional flow simulations to analyze the head and flow rate of the thrust-ring-pump oil circulatory and cooling system at different conditions.Flowmaster ® software was used for the hydrodynamic simulations which later on had a good agreement with the test results. The simulation results were used in the second step of this study to design the flow passages of the thrust-ring-pump under the restrictions of the diameter and the speed of the thrust ring according to the head and flow rate.…”
mentioning
confidence: 99%
“…The resultant comparison between the experimental and numerical data showed that both models can be used to analyze the cooling system. Lai et al[24] conducted one-dimensional flow simulations to analyze the head and flow rate of the thrust-ring-pump oil circulatory and cooling system at different conditions.Flowmaster ® software was used for the hydrodynamic simulations which later on had a good agreement with the test results. The simulation results were used in the second step of this study to design the flow passages of the thrust-ring-pump under the restrictions of the diameter and the speed of the thrust ring according to the head and flow rate.…”
mentioning
confidence: 99%